MODIFIABLE AND NON-MODIFIABLE RISK FACTORS IN PREDICTING THE RECURRENCE OF ATRIAL FIBRILLATION IN PATIENTS WITH ARTERIAL HYPERTENSION - M. S. Arakelyan; N. G. Poteshkina; P. A. Mogutova (Российский кардиологический журнал, 2012)
Aim. To identify the most important risk factors of recurrent atrial fibrillation (AF) and their prognostic value in patients with arterial hypertension (AH). Material and methods. In total, the study included 60 patients with Stage 1–3 AH (Grade I–III, cardiovascular risk 2–4): 20 with the first episode of AF (33%) and 40 with recurrent AF (67%). In all patients, sinus rhythm was restored with pharmacological or electric impulse therapy. At baseline and 6 months after restoring sinus rhythm, the assessment of medical history, antihypertensive and antiarrhythmic therapy, echocardiography, and Doppler ultrasound were performed. To identify silent cardiac arrhythmias and conductivity disorders, Holter electrocardiography monitoring was performed; coronary heart disease was verified with the bicycle stress test. Statistical analyses were performed using the Statistica 6.0 software. Results. The early recurrence of AF was associated with Stage 3 AH, AF in anamnesis, and left atrium dilatation. Conclusion. The combination of Stage 3 AH, AF in anamnesis, and left atrium dilatation was associated with a higher risk of recurrent AF, compared to each of these factors in isolation.